Impacts of Cu deficiency on the thermoelectric properties of Cu2−XSe nanoplates. (July 2016) - Yang, Lei; Chen, Zhi-Gang; Han, Guang; Hong, Min; Zou, Jin
Abstract: Non-stoichiometric Cu2−x Se is one of important thermoelectric candidates for intermediate temperature applications with intrinsically high performance at 800–1000 K. In this study, Cu-deficient Cu2−x Se nanoplates were synthesized by a facile and controllable solvothermal method and the impact of Cu deficiency on their corresponding thermoelectric performance was systematically investigated. It has been found that α-phased Cu2−x Se can be induced by a relatively high level of Cu deficiency (Cu1.95 Se) in the as-synthesized Cu2−x Se nanoplates at room temperature. The Cu deficiency was also found to reduce the thermoelectric performances, but had no significant impact to the morphology of as-synthesized products. Overall, with the existence of full-spectrum phonon scattering mechanism benefited from the nanostructuring, the stoichiometric Cu2 Se nanoplates showed an outstanding ZT of 1.82 at ∼850 K due to its significantly reduced thermal conductivity. With increasing the Cu deficiency, although the Cu2−x Se nanoplates showed a reduced ZT, such as 1.4 at 850 K for Cu1.98 Se, it is still much higher than its bulk counterparts under the same temperature. Graphical abstract: